The impact of the science technology society (STS) approach on critical thinking ability and student learning outcomes. Issue 1 (May 2021) - Mulyanti, S; Halim, A; Murniati,; Ilyas, S; Syukri, M; Mursal,
Abstract: The research objective was to determine the application of the science and technology society (STS) approach in improving critical thinking ability (CTA) and student learning outcomes (LO) at High School Darul Ihsan Aceh Besar. This study used a pre-experimental method with a One Group Pre-test Post-test design. The instrument used in this study was a measurement test of critical thinking ability and learning outcomes. The results of descriptive data analysis show that the application of the Science-Technology-Society approach can improve critical thinking ability and can improve student-learning outcomes in the topic of harmonic oscillation. Besides, it also shows that the post-test score reaches the average value of 88.3 and the average N-gain reaches 75 points that is included in the high criteria of gains. The results of study shows that the science and technology approach to society can improve critical thinking ability and better learning outcomes, especially in the topic of harmonic oscillation.